PREEMPTIVE AND NON-PREEMPTIVE GOAL PROGRAMMING APPROACH TO INVENTORY OPTIMIZATION OF THE CENTRAL STERILE SUPPLY DEPARTMENT, UNIVERSITY COLLEGE HOSPITAL, IBADAN, NIGERIA - MOJISOLA BOLARINWA; KHALID BELLO; PAUL ADEOSUN (Journal of Engineering Studies and Research, 2024)
This research applied a multi-criteria optimization technique to analyse the inventory system of a Central Sterile Supply Department (CSSD) through preemptive and non-preemptive goal programming. Data on six raw materials and four finished products were collected, in addition to their costs, demand rates, shelf lives, and available capital. The developed objective function of the non-preemptive model combined four goals: inventory cost optimization (highest priority), inventory turnover, service level, and delivery lead time. The implemented model guaranteed zero stock-outs, reduced wait times between productions, timely product sales, and the elimination of unnecessary overall costs.